ARSENIC, NICKEL AND LEADREMOVAL FROM UNDERGROUND WELLS BY ADSORPTION ON LATERITE SOIL - OUATTARA, Sinaly; MANGOU-ALLALI, A.Lydie; AMA-CAUPHYS, A.B.; COULIBALY, Lacina (International Journal of Engineering Technologies and Management Research, 2018)
The pollution by heavy metal in the environment, particularly groundwater, constitutes an environmental problem and health in Côte d’Ivoire. Among methods used for removal heavy metals, adsorption by natural absorbent such as a laterite is effective and cheap when compared to other methods. So, this study evaluates the laterite reactor performance for effective removal of heavy metals viz., arsenic (As), nickel (Ni) and lead (Pb) from real-life groundwater. And adsorption of heavy metals was performed with laterite of different particle sizes, viz. coarse grain size of laterite (LRCOG) and laterite granules (LRG). The results obtained showed that the percentages of removal of heavy metal are higher than the size of the laterite. As, Ni and Pb removal are 98.3 ± 0.4%, 99.2 ± 0.2% and 96.1 ± 1.1% respectively in LRCOG effluents. With the laterite in form of granules, percentage removal were of 98.6 ± 0.3% for As that of the Ni is of 99.7 ± 0.2% and 97.9 ± 0.5 % for Pb. The adsorption of heavy metal on the two types of laterite particle size is in the same order of effectiveness: Ni˃As˃Pb.